Functional Characterization of PyrG, an Unusual Nonribosomal Peptide Synthetase Module from the Pyridomycin Biosynthetic Pathway. (9th June 2016) - Huang, Tingting; Li, Lili; Brock, Nelson L.; Deng, Zixin; Lin, Shuangjun
Abstract: Pyridomycin is an antimycobacterial cyclodepsipeptide assembled by a nonribosomal peptide synthetase/polyketide synthase hybrid system. Analysis of its cluster revealed a nonribosomal peptide synthetase (NRPS) module, PyrG, that contains two tandem adenylation domains and a PKS‐type ketoreductase domain. In this study, we biochemically validated that the second A domain recognizes and activates α‐keto‐β‐methylvaleric acid (2‐KVC) as the native substrate; the first A domain was not functional but might play a structural role. The KR domain catalyzed the reduction of the 2‐KVC tethered to the peptidyl carrier protein of PyrG in the presence of the MbtH family protein, PyrH. PyrG was demonstrated to recognize many amino acids. This substrate promiscuity provides the potential to generate pyridomycin analogues with various enolic acids moiety; this is important for binding InhA, a critical enzyme for cell‐wall biosynthesis in Mycobacterium tuberculosis . Abstract : An unusual NRPS‐PKS hybrid domain PyrG controls formation of the enolic acid moiety in pyridomycin biosynthesis. The biochemical characterization of PyrG provides the potential to generate analogues of the antimycobacterial pyridomycin with various enolic acids moiety.